Farmers' work‐day noise exposure. (April 2015) - Williams, Warwick; Brumby, Susan; Calvano, Adrian; Hatherell, Tracey; Mason, Heidi; Mercer‐Grant, Cate; Hogan, Anthony
Abstract Objective This study aims to understand the extent of farmers' exposure to hazardous noise, and trial and test the ability of an on‐farm noise audit report to improve awareness and preventative action towards farm based noise hazards. Design Visits were made to working farms where noise and dosimetry measurements undertaken. During return visits, the noise measurements were explained in a brief report. A follow‐up questionnaire was implemented gathering feedback on the use or otherwise of the report. Setting Working farms in Western Victoria and SE Queensland including dairy, beef, wool, prime lamb and cropping. Participants Participants were 14 female and 37 male farm workers. Interventions Noise exposure assessment of daily activities through dosimetry; measurements of noisy tasks and machinery; supply and interpretation of a noise audit report. Main outcome measures Participants were supplied with a 'noise report' of their workplace together with an explanation of the report's meaning to farm workers. Results Men and women have similar at risk exposures. The average noise exposure was 1.09 Pa2h (LAeq, 8h = 85.3 dB). This implies 163 000 Australian agricultural workers are at risk from hazardous noise. On‐farm noise audit reports were a relevant and valuable feedback to farmers in relation to their potential noise hazards. Conclusions Of those measured 51%, and by extrapolation 163 000 Australian agricultural workers, have noise exposure levels greater than the recommended Australian Standard of 1.01 Pa2h (85 dB). Men and women are equally exposed. On‐farm noise audit reports are an effective feedback to increase awareness and improve hearing health.